The Economics of Comparable Worth - Agarwal, Naresh C. (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "The Economics Of Comparable Worth," by Mark R. Killingsworth.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Equal pay for equal work; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z